Performance analysis of multicore processors using multi-scaling techniques - Jwan Mohammed; Diary R. Sulaiman (Institute of Advanced Engineering and Science, 2023)
Integrating more cores per chip enables more programs to run simultaneously, and more easily switch from one program to another, and the system performance will be improved significantly. However, this current trend of central processing unit (CPU) performance cannot be maintained since the budget of power per chip has not risen while the consumption of power per core has slowly reduced. Generally, the processor’s maximum performance is proportional to the product of the number of their cores and the frequency they are running at. However, this is usually limited by constraints of power. In this study, first, the voltage/frequency adjustment of the running cores has been analyzed for several programs to improve the processor’s performance within the constraint of power. Second, the impact of dynamically scaling the number of running cores is summarized for additional performance improvements of the active programs and applications. Finally, it has been verified that scaling the number of the running cores and their voltage/frequency simultaneously can improve the processor’s performance for a higher power dissipation or under power constraints. The performance analysis and improvements are obtained in a real-time simulation on a Linux operating system using a GEM5 simulator. Results indicated that performance improvement was attained at 59.98%, 33.33%, and 66.65% for the three scenarios, respectively.